Nanostructured 2D Materials: Prospective Catalysts for Electrochemical CO2 Reduction. Issue 1 (28th November 2016) - Liu, Jinlong; Guo, Chunxian; Vasileff, Anthony; Qiao, Shizhang
Abstract : Electrochemical CO2 reduction to useful fuels and chemicals, driven by renewable energy from intermittent sources such as solar and wind, has been keenly pursued in recent years as a means to resolving energy security and environmental issues associated with conventional fossil fuels. Nanostructured two‐dimensional (2D) materials, possessing abundant active sites in the form of surface atoms and edge sites, and providing better electrical conductivity along 2D conducting channels, represent promising candidates for high‐performance CO2 ‐reduction electrocatalysts. Here, newly developed nanostructured 2D materials, including atomically thin transition‐metal/metal oxides, transition‐metal dichalcogenides, and metal‐free 2D materials, are highlighted as state‐of‐the‐art catalysts toward electrochemical CO2 reduction. Through further exploration of new nanostructured 2D materials and their nanocomposites, more and more breakthroughs in this field of research are to be expected. Abstract : Nanostructured 2D materials, in particular atomically thin transition metals/metal oxides, nanostructured transition‐metal dichalcogenides, and metal‐free 2D materials, are highlighted as state‐of‐the‐art electrocatalysts for CO2 reduction, achieving high activity, good selectivity, and stability in operation. Future development of new 2D nanomaterials and their nanocomposites with tailored physicochemical properties will greatly advance this research field.